Serum Proteinogram of Chinese Goose (Anser cygnoides) Vaccinated or Not Against Newcastle Disease - Paulillo, Antonio Carlos; Campioni, Josie Maria; Schmidt, Elizabeth Moreira dos Santos; Santana, Andre Marcos; Fagliari, Jose Jurandir; Testi, Alan Jonathan Pereira; Denadai, Janine (International Journal of Poultry Science, 2009)
The blood proteinogram was investigated in Chinese geese vaccinated or not against Newcastle disease, using Ulster 2C, B1 and LaSota strains. Total serum protein, globulins and albumin/globulin ratio showed no significant differences between birds vaccinated or not against Newcastle disease. Albumin concentration was significantly lower in 42 day-old Chinese geese vaccinated with LaSota strain.